Pengenalan Pupuk Organik Cair dan Sistem Biopori di Kampung Babakan, Tangerang - Karnelasatri; Kelly Sinaga; Candra Yulius Tahya; Debora Sitinjak; Friska Juliana Purba (Institut Pertanian Bogor, 2021)
Every year waste production has increased because of human population growth in Indonesia. The most waste component is organic waste, which contributes a negative impact on the environment and human health. This situation is also discovered in the Babakan Sub-village, Binong, Tangerang District. The awareness of the society related to waste management is needed to improve due to the garbage in this village is not managed properly. Moreover, a high frequency of flooding has happened in this area during the rainy season. To deal with this problem, the community service team of Pelita Harapan University introduced a biopori system and organized a workshop to produce liquid organic fertilizer. The purpose of this activity was to raise awareness of waste management in the society of Babakan related to waste management and environmental health. The method used was the field observation and community education that was counseling and workshop. The service had been going great and the society of Babakan village, Tangerang, gave a positive and active response. These community services caused the society of Babakan, Binong, Tangerang to get new options to manage their waste more properly.